Evaluasi Pelaksanaan Pendidikan Sekolah Dasar Unggul di Sekolah Dasar Negeri Kauman II Malang - - Sutrisno (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this qualitative classroom action research is to evaluate the educational implementation in the excellent school based on some criteria, i.e. physical and social environment, students selection methods, teachers’ recruitment, understanding and implementation of curriculum, facilitation, school management, and funding. The objects of this research were SDN Kauman II Malang. Results found that most of the criteria were fulfilled by the school.